Accuracy of diagnostic testing in primary ciliary dyskinesia. Issue 3 (3rd December 2015) - Jackson, Claire L.; Behan, Laura; Collins, Samuel A.; Goggin, Patricia M.; Adam, Elizabeth C.; Coles, Janice L.; Evans, Hazel J.; Harris, Amanda; Lackie, Peter; Packham, Samantha; Page, Anton; Thompson, James; et al.
Diagnosis of primary ciliary dyskinesia (PCD) lacks a "gold standard" test and is therefore based on combinations of tests including nasal nitric oxide (nNO), high-speed video microscopy analysis (HSVMA), genotyping and transmission electron microscopy (TEM). There are few published data on the accuracy of this approach. Using prospectively collected data from 654 consecutive patients referred for PCD diagnostics we calculated sensitivity and specificity for individual and combination testing strategies. Not all patients underwent all tests. HSVMA had excellent sensitivity and specificity (100% and 93%, respectively). TEM was 100% specific, but 21% of PCD patients had normal ultrastructure. nNO (30 nL·min −1 cut-off) had good sensitivity and specificity (91% and 96%, respectively). Simultaneous testing using HSVMA and TEM was 100% sensitive and 92% specific. In conclusion, combination testing was found to be a highly accurate approach for diagnosing PCD. HSVMA alone has excellent accuracy, but requires significant expertise, and repeated sampling or cell culture is often needed. TEM alone is specific but misses 21% of cases. nNO (≤30 nL·min −1 ) contributes well to the diagnostic process. In isolation nNO screening at this cut-off would miss ∼10% of cases, but in combination with HSVMA could reduce unnecessary further testing. Standardisation of testing between centres is a future priority. Combination testing in PCD diagnosis remains the most accurate approach, but standardisation is needed http://ow.ly/TLEDu